Agile-Based Application Architecture Design for Billet Management in Industrial Manufacturing - Ramadhani, Rafian; Hizbullah, Fauzi; Auliya Rahman, Ilham; Ahyar Harizillah, M.; Noorachmad Muttaqin, Alif; Saidi Lubis, Fahdi (Electronic Integrated Computer Algorithm Journal, 2025)
This study presents the planning and iterative development of an enterprise application architecture for the Billet Stacker Rail system in an aluminum manufacturing environment. The system is designed to enhance the management of billet logistics, including receiving, inspection, stacking, and transfer processes. Using the Agile methodology, particularly the Scrum framework, the development team collaborated closely with operational stakeholders to capture requirements and validate functionality through a series of Sprints. The process included modeling workflows, designing class and entity diagrams, and creating interactive user interface mockups. The system architecture was developed incrementally to support modularity, traceability, and real-time data recording. Each component from billet tracking to user management was prototyped and refined based on continuous feedback. The Agile approach facilitated rapid adjustments to changing requirements, reduced development risk, and supported a user-centered design process. The result is a robust and scalable application blueprint that aligns with the industrial environment’s needs for efficiency, reliability, and transparency in billet management operations.